S-PRG Filler Eluate Induces Oxidative Stress in Oral Microorganism: Suppression of Growth and Pathogenicity, and Possible Clinical Application - Yu Kono; Muneaki Tamura; Marni E. Cueno; Morio Tonogi; Kenichi Imai (MDPI AG, 2021)
Controlling the oral microbial flora is putatively thought to prevent not only oral diseases, but also systemic diseases caused by oral diseases. This study establishes the antibacterial effect of the novel bioactive substance "S-PRG filler" on oral bacteria. We examined the state of oxidative stress caused by the six types of ions released in eluate from the S-PRG filler in oral bacterial cells. Moreover, we investigated the effects of these ions on the growth and pathogenicity of Gram-positive and Gram-negative bacteria. We found that the released ions affected SOD amount and hydrogen peroxide in bacterial cells insinuating oxidative stress occurrence. In bacterial culture, growth inhibition was observed depending on the ion concentration in the medium. Additionally, released ions suppressed Streptococcus mutans adhesion to hydroxyapatite, S. oralis neuraminidase activity, and Porphyromonas gingivalis hemagglutination and gingipain activity in a concentration-dependent manner. From these results, it was suggested that the ions released from the S-PRG filler may suppress the growth and pathogenicity of the oral bacterial flora. This bioactive material is potentially useful to prevent the onset of diseases inside and outside of the oral cavity, which in turn may have possible applications for oral care and QOL improvement.